Konseling Paska Bencana: Tela’ah atas Konsep dan Terapi Post Traumatic Stress Disorder - Effendi Dudy Imanudin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2010)
Helping to client who suffer because of calamity victim need the different specific paradigm of the public service shapes apllied in conventional approach. Service shape have character as social-psychology, stressing to urgency of socius environment and social system in helping to return psychological condition of post calamity client. The excellent of this approach not only in preventive effort, promotive, rehabilitative and liberative., but also based to three ideas as: holistic human, integrated approach, humn caring and encountering nature.